La educación y formación integral biopedagógica en farmacoseguridad (2019)
ABSTRACT: The present work aims to analyze, based on various research papers, the perception of education and formation of the human talent suitable for abilities and capacities that allows people to explain, through the cognitive pharmaceutical attention and the pharmacotherapeutic follow- up, the risk factors of the use of drugs. For this, we extracted 43 research papers published between 2005 and 2014, written in English or Spanish, published in Latin America. In these articles seven categories should be found: medicines, health, disease, human talent, and biomedical sciences. The extraction of the articles was done using the Google Academic advanced search tool. To analyse the findings, focused on the previously mentioned categories, a FLOR matrix was used, which considers Strengths, Achievements, Opportunities and Challenges linked to the categories studied from the perspective of education and comprehensive training of students and professionals of the health. Finally, it is concluded that the common objective should be to train comprehensively the human talent in a broader scientific knowledge about pharmacological safety, related to other biomedical and humanistic learning, through a multicultural transdisciplinary team that allows the promotion of the rational use of medicines, in compliance with the responsibility and social function of pharmacist.